The fetal programming effect of prenatal smoking on Igf1r and Igf1 methylation is organ- and sex-specific - Karolin F. Meyer; Rikst Nynke Verkaik-Schakel; Wim Timens; Lester Kobzik; Torsten Plösch; Machteld N. Hylkema (Epigenetics, 2017)
The impact of prenatal smoke exposure (PSE) on DNA methylation has been demonstrated in blood samples from children of smoking mothers, but evidence for sex-dependent smoke-induced effects is limited. As the identified differentially methylated genes can be associated with developmental processes, and insulin-like growth factors (IGFs) play a critical role in prenatal tissue growth, we hypothesized that PSE induces fetal programming of Igf1r and Igf1. Using a mouse model of smoking during pregnancy, we show that PSE alters promoter methylation of Igf1r and Igf1 and deregulates their gene expression in lung and liver of fetal (E17.5) and neonatal (D3) mouse offspring. By further comparing female versus male, lung versus liver, or fetal versus neonatal time point, our results demonstrate that CpG site-specific aberrant methylation patterns sex-dependently vary per organ and time point. Moreover, PSE reduces gene expression of Igf1r and Igf1, dependent on organ, sex, and offspring's age. Our results indicate that PSE may be a source of organ-specific rather than general systemic fetal programming. This is exemplified here by gene promoter methylation and mRNA levels of Igf1r and Igf1, together with a sex- and organ-specific naturally established correlation of both parameters that is affected by prenatal smoke exposure. Moreover, the comparison of fetuses with neonates suggests a CpG site-dependent reversibility/persistence of PSE-induced differential methylation patterns.